2016
DOI: 10.1038/srep29208
|View full text |Cite
|
Sign up to set email alerts
|

New insight into the dynamical system of αB-crystallin oligomers

Abstract: α-Crystallin possesses a dynamic quaternary structure mediated by its subunit dynamics. Elucidation of a mechanism of subunit dynamics in homo-oligomers of αB-crystallin was tackled through deuteration-assisted small-angle neutron scattering (DA-SANS) and electrospray ionization (ESI) native mass spectrometry (nMS). The existence of subunit exchange was confirmed with DA-SANS, and monomers liberated from the oligomers were observed with nMS. With increasing temperature, an increase in both the exchange rate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 27 publications
3
47
0
Order By: Relevance
“…It is well known that the dynamics and polydispersity of oligomers play an important role in the functioning of α-crystallins [ 10 , 29 , 90 , 91 ]. It was reported that subunit exchange promotes structural reorganization within the homo-oligomers of αB-crystallin [ 27 ] (see review [ 29 ]). The equilibrium between oligomeric forms is very sensitive to many factors such as temperature [ 1 , 27 , 92 , 93 , 94 ], post-translational modifications (phosphorylation) [ 33 , 35 , 95 ], divalent cations [ 31 , 32 ], crowding conditions [ 25 ], presence of target protein [ 25 ], and many others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that the dynamics and polydispersity of oligomers play an important role in the functioning of α-crystallins [ 10 , 29 , 90 , 91 ]. It was reported that subunit exchange promotes structural reorganization within the homo-oligomers of αB-crystallin [ 27 ] (see review [ 29 ]). The equilibrium between oligomeric forms is very sensitive to many factors such as temperature [ 1 , 27 , 92 , 93 , 94 ], post-translational modifications (phosphorylation) [ 33 , 35 , 95 ], divalent cations [ 31 , 32 ], crowding conditions [ 25 ], presence of target protein [ 25 ], and many others.…”
Section: Discussionmentioning
confidence: 99%
“…HSPB5 tends to form large polydisperse assemblies ranging from 10-mer to 40-mer and higher, having very dynamic structures [ 19 , 23 , 24 , 25 ]. All oligomeric forms possess chaperone-like activity and easily exchange their subunits [ 20 , 26 , 27 ]. It is well accepted that a flexible dynamic quaternary structure is necessary for sHSPs activity [ 1 , 4 , 10 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the solution-state conditions allow kinetic, i.e. time-resolved, SANS studies to be carried out, for example on the assembly process of proteasome subunits (Sugiyama et al, 2011), -crystallin oligomerization dynamics (Inoue et al, 2016;Fig. 3a) and the enzyme-mediated unfolding of GFP (Ibrahim et al, 2017;Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recent examples from the literature illustrating the versatility of Bio-SANS. (a) Models proposed for the -crystallin oligomerization process using a kinetic SANS study of mixtures of hydrogenated and deuterated building blocks(Inoue et al, 2016). (b) Enzyme-mediated unfolding of GFP measured by time-resolved SANS(Ibrahim et al, 2017).…”
mentioning
confidence: 99%